Management of patients with low back pain: a survey of French chiropractors - Debarle, Michel (BioMed Central, 2014)
BACKGROUND: Little is known about the level of consensus within the French chiropractic profession regarding management of clinical issues. A previous Swedish study showed that chiropractors agreed relatively well on the management strategy for nine low back pain scenarios. We wished to investigate whether those findings could be reproduced among French chiropractors. OBJECTIVES: 1. To assess the level of consensus among French chiropractors regarding management strategies for nine different scenarios of low back pain. 2. To assess whether the management choices of the French chiropractors appeared reasonable for the low back pain scenarios. 3. To compare French management patterns with those described in the previous survey of Swedish chiropractors. METHOD: A postal questionnaire was sent to a randomly selected sample of 167 French chiropractors in 2009. The questionnaire described a 40-year old man with low back pain, and presented nine hypothetical short-term outcome scenarios and six possible management strategies. For each of the nine scenarios, participants were asked to choose the management strategy that they would recommend. The percentages of respondents choosing the different management strategies were identified for each scenario. Appropriateness of the chosen management strategy was assessed using predetermined “best practice” for each scenario. Consensus was arbitrarily defined as “moderate” when 50- 69% of respondents agreed on the same management choice for a scenario, and “excellent” when 70% or more provided the same answer. RESULTS: Excellent consensus was achieved for only one scenario, and moderate consensus for two scenarios. For five of the nine scenarios, the most common answers were in agreement with the “best practice” management strategies. Consensus between the French and Swedish responses on the most appropriate management was seen in five of the nine scenarios and these were all in agreement with the expected answer. CONCLUSION: There was reasonable consensus among the French chiropractors in their choice of treatment strategy for low back pain and choices were generally in line with “best practice”. The differences in response between the French and Swedish chiropractors suggest that cultural and/or educational differences influence the conceptual framework within which chiropractors practice.